Analysis of fatigue in surgeons after simultaneous laparoscopic operations - Halei, M.; Dzubanovskyi, I.; Marchuk, I. (Journal of Education, Health and Sport, 2020)
Fatigue is a temporary decrease in the efficiency of an organism or organ due to intensive or long-term work, which is manifested in a decrease in quantitative and qualitative indicators of work and deterioration of coordination of work functions. Groups of simultaneous operations (411 patients) and group of single operations (746 patients) were formed. The frequency of fencing also depended on the type of the body type of the patient, but with recalculation and averaging it was similar in both groups (4.18 ± 0.228 for their own method and 3.98 ±0.201 inthe group of standard equipment). The similarity and severity and nature of changes in both groups are very noticeable on the diagrams. The changes are comparable, and are easily explained by the longer operation time and the larger amount of work, in comparison with the usual technique of one operation. Also, the changes did not exceed 15%, which indicates a slight work fatigue, and does not lead to overfatigue. Our developed technique of simultaneous laparoscopic operations is effective and safe. It provides acceptable level of ergonomics and does not increase physical or mental pressure on surgeon.